Online Political Communication: Identity, e-representation and Self-presentation on Women's Legislatif Members - annafi FSM, Nur’; Mustika Elita, Funny; Rijal, Edwin; Mulyana, Slamet (International Journal of Psychosocial Rehabilitation, 2020)
The paper in this study has a goal to examine how political interactions are carried out in online media used by Instagram and Facebook platforms. Through the analysis of online content, this study concentrates on how online media can be used by women legislators as political media for delivering messages to netizens (the public) and can change their identity. The results of this study indicate that there are many women legislators in Indonesia, but not all are active users of online media, both for self-interest and institutional interests. Members of the legislature promote themselves by portraying themselves in online media as representatives of the people who are responsible for their mandate, namely as a placeholder for people's aspirations. The legislative members promote themselves by portraying themselves as human beings who have freedom, not as representatives of the people. In contrast to other women's legislative members, they want to be interpreted as people who love their family so much that their posts are family photos, cooking food for the family. The diversity of interpretations in social media for users is related to her, her family, her studies, her hobbies, her community, and her work.